Nossa Senhora Integradora dos Mundos: o mito mariano e a potência imagético-comunicativa do arquétipo do Grande Feminino - Machado, Patricia Santos (2021)
The proposal that permeates this thesis is to enter the world of popular devotion around the image of Our Lady, aiming to understand the communication processes in audiovisual productions and the influences of symbolic-imaginary constructions on culture and collective identities. The corpus of this research includes the narrative of the film documentary Marias: Faith in the Feminine (Brazil, 2016), in which the hybrid nuances of the Marian faith in five Ibero-American countries are portrayed. The objective is to investigate the communicative complexity of the narratives and of Our Lady present in the manifestations of popular religiosity. Such religiosity, characterized by the influx of Iberian Catholicism and steeped in contents of European, Amerindian and African ancestral traditions, seems to us related to the processes of overcoming dichotomies and borders between cultures and collective identities. Our hypothesis is that the communicational processes involving the image of Our Lady manifest the mediating and aggregating potential of the Great Feminine and that such imagery-communicative power of the archetype is able to unite the worlds separated by dualistic logic, by fragmenting ideologies and by religious dogmas. Such worlds – or dimensions – can be exemplified here, such as: the spiritual and the material; the sacred and the profane; the feminine and the masculine; life and death; body and soul and also women and men, poor and rich, traditionalists and progressives, etc. Our research has as an interdisciplinary theoretical basis: the studies of social imaginary and comparative mythology; Jungian studies; visual culture; cultural studies; and also research on communication and religion. The methodological path was developed from the tools of HP (Depth Hermeneutics), conceived by J.B. Thompson, in dialogue with the methods of our theoretical-methodological basis, such as Aby Warburg's studies on images and visual culture. This methodological conjunction meets the complex nuances of our object of analysis. Furthermore, we included methodological experimentation in the process, which we called the Imagetic-communicative Atlas. The Atlas is composed of research and categorization of cultural and media products correlated with the figure of Mary; for the elaboration of image panels and, in this phase of the method, for the descriptive iconographic analysis of the selected phenomena. The results achieved in this work show that the construction of the multifaceted Marian image and its mythical-religious narratives comprises complex processes of encounters, dialogues, hybridizations and symbolic, religious, cultural and identity fusions that are sometimes conflicting and contradictory, but also they are conciliatory. We also observe that the figure of Our Lady transits through history, religions and cultures and is equally present in the most varied media and communication processes – overcoming the divisions between the sacred and the profane, among other dichotomies. From a deeper perspective and beyond the limitations of the materialist view, we conclude that the imagery and narrative elements present in the phenomena involving the faces of Our Lady are mainly from the transpersonal contents present in the collective unconscious and in the social imaginary. Such contents are related to what we call the imagetic-communicative potency of the Great Feminine archetype(AU)